Budget Absorption: on The Interaction of Organizational Commitment, Budget Planning and Quality of Human Resources of The OPD in Serang City - Fara Fitriyani; Nana Nofianti; Leni Oktaviani (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to examine the effect of budget planning, the quality of human resources on budget absorption with organizational commitment as a moderating variable (empirical study Of the OPD  on Serang City). This research is a type of quantitative research, data is collected by distributing questionnaires directly with purposive sampling technique to the respondents. While the respondents are functional officials in agencies/work units within the Serang City government who are certainly involved in the budgeting process, with a total of 90 respondents who can be processed. The analytical method used in this study is moderate regression analysis (MRA).  From the results of moderate regression analysis (MRA), four hypotheses show their effect on budget absorption, namely: 1) budget planning has a significant effect on budget absorption 2) quality of human resources has a significant effect on budget absorption 3) the interaction between budget planning and organizational commitment as a moderating variable has a significant effect on budget absorption 4) the interaction between the quality of human resources and organizational commitment as a moderating variable has a significant effect on budget absorption